Some thoughts on the relationship between law and religion in Malaysia - Ab Aziz, Shamrahayu (CLJ Legal Network Sdn Bhd, 2009)
Malaysia is moulded in and impressed with religious values and traditions. This remains a strong essential feature of the basic fabric of the Malaysian society. Religion, in one way or another, is seen as having a special position in Malaysia especially when the Constitution establishes a state religion. Despite that, several issues arise in the relationship between law and religion in the country, such as should religion be a basis in the making or the enforcement of the law. This paper discusses the relationship between state and religion in Malaysia with an emphasis on the state-religion relationship from constitutional perspective and the position of religion in the country's law and legal system. Various relevant constitutional provisions, legislation and court decisions are analysed in order to discuss and explain the relationship between law and religion in Malaysia. This paper fmds that both the constitutional/legal facts and the sociological facts of the country play an important role in identifying the relationship between law and religion in Malaysia.